2018
DOI: 10.14254/2071-8330.2018/11-4/11
|View full text |Cite
|
Sign up to set email alerts
|

Endogeneity of money: The case of Сzech Republic

Abstract: The goal of this paper is to specify the trends of money supply in Czech Republic. This will allow us evaluate the current approach taken by the Czech National Bank in its monetary policy. To determine money's endogeneity, we have analyzed time series for the M3 monetary aggregate, the monetary base, GDP, and loans. As part of the analysis, we have worked with quarterly data from the 1 st quarter of 1996 to the 2 nd quarter of 2017. We determined the optimal lag time for the time series using the Hannan-Quinn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies confirm the important role of the monetary sector on economic growth in various countries (Černohorská, 2018;Sirag et al, 2018;Tule et al, 2018). The monetarist view states that money supply and economic activity has a positive relationship.…”
Section: Related Literaturementioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies confirm the important role of the monetary sector on economic growth in various countries (Černohorská, 2018;Sirag et al, 2018;Tule et al, 2018). The monetarist view states that money supply and economic activity has a positive relationship.…”
Section: Related Literaturementioning
confidence: 69%
“…Some papers mention that expansive fiscal policy has positive effects on economic growth (Auerbach, Gale, & Harris, 2010;Nguyen, 2015;Raji, Juzhar, & Jantan, 2014). Likewise, the expansive monetary policy is also the main factor in supporting economic growth in various countries (Černohorská, 2018;Sirag, SidAhmed, & Ali, 2018;Tule, Ogundele, & Apinran, 2018). Therefore, we may infer that the expansive fiscal and monetary policies will encourage economic growth sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study only involves one variable as a determinant of economic growth that is final energy consumption. Some previous research that focuses on economic growth determinants generally mentions several variables such as capital, labor, natural resources and government policies (Bošnjak, 2018;Černohorská, 2018;Hodula and Pfeifer, 2018). Based on these studies, we may highlight that economic growth is affected by various variables such as energy consumption, fiscal and monetary policies.…”
Section: Related Literaturementioning
confidence: 95%
“…For example, Oguzhan and Ethem (2017) found that for Turkey, the causality runs from bank loans to money supply, which supports the endogenous view that the central bank fully meets the total demand for money. Similarly, Cernohorská (2018) showed the monetary base to be endogenous for the Czech Republic. In contrast, Thenuwara and Morgan (2015) in the test of the endogenous money theory found the broad money multiplier to be unstable, casting doubt on the effectiveness of money targeting in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%